Asymmetric timely loss recognition, adverse shocks to external capital, and underinvestment: Evidence from the collapse of the junk bond market - Kim, Jaewoo (Journal of Accounting and Economics, 2018)
Using the collapse of the junk bond market in the early 1990s as an exogenous shock to external capital, I document, in both difference-in-differences and triple difference designs, that speculative-grade firms that recognize economic losses in a timely manner experience a smaller reduction in investment following the collapse. The effect is more pronounced for speculative-grade firms with a low level of asset liquidation value. Using the excess bond premium as a proxy for fluctuations in the supply of capital, I also extend the generalizability of my findings to a broader sample of 84,421 firm-years over the 1972–2011 period.